Two hot to handle: How do we manage the simultaneous impacts of climate change and natural disasters on human health? - Phalkey, Revati; Louis, Valérie R. (European physical journal special topics, 2016)
Climate change is one of the major challenges we face today. There is recognition alongside evidence that the health impacts of both climate change and natural disasters are significant and rising. The impacts of both are also complex and span well beyond health to include environmental, social, demographic, cultural, and economic aspects of human lives. Nonetheless integrated impact assessments are rare and so are system level approaches or systematic preparedness and adaptation strategies to brace the two simultaneously particularly in low and middle-income countries. Ironically the impacts of both climate change as well as natural disasters will be disproportionately borne by low emitters. Sufficiently large and long-term data from comprehensive weather, socio-economic, demographic and health observational systems are currently unavailable to guide adaptation strategies with the necessary precision. In the absence of these and given the uncertainties around the health impact projections alongside the geographic disparities even within the countries, the main question is how can countries then prepare to brace the unknown? We certainly cannot wait to obtain answers to all the questions before we plan solutions. Strengthening health systems is therefore a pragmatic “zero regrets” strategy and should be adopted hastily before the parallel impacts from climate change and associated extreme weather events (disasters thereof) become too hot to handle